Wykorzystanie zysku ekonomicznego w ocenie przedsiębiorstw i instytucji finansowych - Marcinkowska, Monika (The Use of Economic Profit Companies and Financial Institutions Evaluation, 2008)
Economic profit includes the cost of equity and therefore enables the full performance evaluation. If it is positive - revenues have covered the costs of all production factors, including capital, and additional value is created; if it is negative - value is destructed. The paper presents the main areas of use of EP concept: strategic management, pricing, performance evaluation of entity and its internal units (showing rules of internal cost of equity measurement). The ways of improving economic profit value are also presented, as well as how it is shifted to market value added.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 375-384